Procedures & guidelines for a regional mechanism for accreditation, equivalency and articulation (Association of Caribbean Tertiary Institutions Inc [Bridgetown]BB, 2000)
Seeks to provide practical ways of dealing with issues of accreditation, equivalence and articulation within a regional framework.
Keywords: ADMISSION REQUIREMENTS